Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.3 - Derivatives of Trigonometric Functions - 3.3 Exercises - Page 196: 6



Work Step by Step

$g(\theta)=e^{\theta}(\tan\theta-\theta)$ Differentiate using the product rule: $g'(\theta)=(e^{\theta})(\tan\theta-\theta)'+(\tan\theta-\theta)(e^{\theta})'=...$ $...=(e^{\theta})(\sec^{2}\theta-1)+(\tan\theta-\theta)(e^{\theta})=...$ We can use the following identity: $\sec^{2}\theta-1=\tan^{2}\theta$: $...=e^{\theta}\tan^{2}\theta+(\tan\theta-\theta)e^{\theta}=...$ Take out common factor $e^{\theta}$ for a better looking answer: $...=e^{\theta}(\tan^{2}\theta+\tan\theta-\theta)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.